The capacitive sensing of NS1 Flavivirus biomarker - Cecchetto, Juliana [UNESP]; Fernandes, Flávio C.B. [UNESP]; Lopes, Rute [UNESP]; Bueno, Paulo R. [UNESP] (Elsevier, 2017)
NS1 is a biomarker for different Flavivirus diseases such as dengue (DENV), zika (ZIKV) and chikungunya (CHIKV) and was herein selectively quantified by electrochemical capacitive sensing (an impedance-derived capacitance methodology wherein the redox probe is contained in the receptive layer) mainly aiming dengue diagnosis in phosphate buffer saline and blood serum environments (up to the neat level). The capacitive sensing was compared to traditional concurrent impedimetric approach (in which the redox probe is added in the biological solution) and other transient methods stated in the literature regarding figures of merit such as limit of detection, linear range, relative standard deviation and affinity constant. Capacitive and impedimetric assays showed equivalent results for linear range, repeatability, sensitivity and constant of affinity. Nonetheless capacitive assays presented better reproducibility with a relative standard deviation (RSD) of 3±1 and 7±4 (all in percentage) in PBS and serum, respectively, meanwhile for impedimetric assays the RSD values were 9±5 in PBS and 12±6 in serum. Thus, by using capacitive assays, an improvement on the analytical performance was observed with the limit of detection about sixty-fold lower in neat serum (∼0.5 ng mL−1 for capacitive over ∼30 ng mL−1 for impedimetric assays) compared to traditional electrochemistry methods in general hence demonstrating the superior detection sensitivity for NS1 protein. Accordingly, redox tagged capacitive assays are suitable for the development of multiplex point-of-care neglected diseases sensing applications.
Keywords: Dengue; Electrochemical capacitance spectroscopy; Electrochemical impedance spectroscopy; Flavivirus; NS1